Roof Stability of Rectangle Coal Roadway: In Light of Calculation of Compressive Bar Stability - Ma Shou-Long; Gao Linsheng; Yang Yue; Peng Rui; Zhao Qifeng (Advances in Civil Engineering)
The roadway roof is a key factor to the roadway stability. The analysis of roof stability is mainly based on numerical calculation and on-site observation, while the basic theory of the bearing mechanism is relatively weak. We have founded a critical pressure calculation model, on the theory of compressive bar, for the rectangle coal roadway stability. The model has been tested and verified on accuracy and feasibility while applied on a roadway case. The critical pressure for roof stability and roof bending moment and deflection under combined axial and lateral load was deduced using the theory of compressive bar stability. The numerical calculation verified the feasibility of numerical modeling of stability of compressive bar using FLAC3D, and the influence of the background ambient horizontal stress and the parameters of the contact surface to the roof stability were further studied. The result turns out that some factors lead to a higher instability tendency, including higher horizontal stress, higher cohesion force, and larger internal friction angle on the coal-rock interface and lower cohesion force and smaller friction angle on the rock-rock interface. The results contribute to bearing mechanisms of roadway roof stability, ground pressure and strata control theory and application, and design of bolting support.